Diagnosis of canine monocytotropic ehrlichiosis: an update review - Rodríguez-Vivas, Roger Iván; Bolio-González, Manuel Emilio; Ojeda-Chi, Melina Maribel (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Canine monocytic ehrlichiosis (CME) is caused by the infection with a rickettsial organism, Ehrlichia canis. This organism is replicated only in the cytoplasm of blood monocytes and tissue macrophages. CME has been reported throughout the world but at higher frequencies in tropical and subtropical regions. CME is often under-recognized since the disease is difficult to diagnose due to variable clinical signs, its different stages, and frequent co—infection with other tick-borne pathogens or other infectious agents. Clinical manifestations and the traditional diagnostic techniques such as hematology and demonstration of typical cytoplasmic E. canis-morulae in monocytes in blood smears have been used for the diagnosis of CME; however, the PCR—based diagnostic tests and serology methods based on specific antigens, are the most sensitive and specific for this disease. This article reviews the current literature covering the diagnosis of infection by E. canis in dogs.